2020
DOI: 10.1111/ppl.13096
|View full text |Cite
|
Sign up to set email alerts
|

Will rising atmosphericCO2concentration inhibit nitrate assimilation in shoots but enhance it in roots ofC3plants?

Abstract: Bloom et al. proposed that rising atmospheric CO 2 concentrations 'inhibit malate production in chloroplasts and thus impede assimilation of nitrate into protein of C 3 plants, a phenomenon that will strongly influence primary productivity and food security under the environmental conditions anticipated during the next few decades'. Previously we argued that the weight of evidence in the literature indicated that elevated atmospheric [CO 2 ] does not inhibit NO 3 − assimilation in C 3 plants. New data for comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…To eliminate the effect of biomass increase, we used the percentage of nitrate-N in total N (nitrate-N content per total N content) as an index of nitrate accumulation. As a result, in most species, we found that eCO 2 decreased (i.e., wheat, potato, and guinea grass) or did not change (i.e., Amaranthus ) nitrate accumulation at the whole-plant level under the nitrate-fed condition ( Figure 1E ; Table 2 ), which likely supports the view of Andrews et al ( 2019 , 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To eliminate the effect of biomass increase, we used the percentage of nitrate-N in total N (nitrate-N content per total N content) as an index of nitrate accumulation. As a result, in most species, we found that eCO 2 decreased (i.e., wheat, potato, and guinea grass) or did not change (i.e., Amaranthus ) nitrate accumulation at the whole-plant level under the nitrate-fed condition ( Figure 1E ; Table 2 ), which likely supports the view of Andrews et al ( 2019 , 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Currently, there are different views on whether eCO 2 inhibits nitrate assimilation in C 3 plants (Bloom et al, 2020 ) or not (Andrews et al, 2020 ). Inhibition of nitrate assimilation under eCO 2 results in nitrate accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, NO3 − assimilation significantly declined on with mutations that nearly eliminated enzyme activities [104,117,118], and 50% higher NO3 − reductase activities did not assimilate more NO3 − [119]. St confused rates of enzyme activities with those of NO3 − assimilation as a wh false conclusions [120,121]. One physiological mechanism that may be responsible for the inter photorespiration and shoot NO3assimilation involves the reduction of complex during oxidation of RuBP.…”
Section: Photorespiration and Other Metabolic Pathwaysmentioning
confidence: 99%
“…On a whole plant basis, elevated CO 2 can increase nitrogen assimilation ( Andrews et al, 2019 ). To date, the mechanisms underlying the effects of elevated CO 2 on chloroplastic nitrogen assimilation in C 3 plants are still unresolved ( Andrews et al, 2020 ; Bloom et al, 2020 ). These different responses might be related to the diversity of plant primary metabolism in C 3 species, reflected in different enzymatic activities and metabolite levels ( Arrivault et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%